Crafting Inclusive Playful Learning Environments: Exploring Affective Strategies and Atmospheres - Skriver, Jennifer Ann (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2024)
This article contributes new critical perspectives to Playful Learning, an emerging educational field rooted in inclusivity, democratic principles, and adaptability. It seeks to bridge the gap between playful learning and affective thinking, exploring how atmospheres can enhance inclusivity within higher educational contexts. Specifically, it investigates artful teaching practices in the Social Education Study Program at a University College in Denmark to uncover affective strategies that foster inclusivity within playful approaches. The article establishes the potential of integrating affect-based thinking in playful learning. It navigates the complexities of the magic circle of play and contextualizes the study within the broader landscape of art education and atmospheres. Drawing from a situated relational approach to affect, it introduces the concept of affective arrangements and atmospheres, showcasing their influence on agency and inclusion. The empirical analysis presents two ethnographic vignettes demonstrating how intentional design choices create atmospheres of inclusion. By shedding light on the interplay between affect, atmospheres, and inclusivity, this article contributes to the emerging field of Playful Learning. It offers critical insights for educators striving to create inclusive playful learning environments.